Characteristics of syngas combustion resulting from coffee husk biomass waste gasification process: Overview of automotive fuel alternatives - Andi Sanata; Imam Sholahuddin; Muhammad Dimyati Nashrullah; Hendry Y. Nanlohy; Mebin Samuel Panithasan (Universitas Muhammadiyah Magelang, 2024)
The production of syngas from coffee husk biomass waste as a raw material offers significant potential as an alternative automotive fuel source through the gasification process, considering the abundant resources available. Therefore, this study aimed to characterize the physical properties of the fuel initially, in order to observe the differences in these properties after the fuel underwent Ultra Fine Bubble treatment. The objective was to analyze the combustion characteristics of syngas derived from coffee husk biomass waste, to develop a sustainable alternative to fossil fuels for automotive applications. The results showed that with increasing air discharge, the concentration of CO and Hâ‚‚ gases in gasified syngas increased while the concentration of CH4 decreased. Additionally, higher air discharge resulted in lower tar content, higher flame temperature, higher flame height visualization, and higher generator power output as a review of the feasibility of alternative automotive fuels.